An Environment to Support Structural Testing of Autonomous Vehicles - Neves, Vania De Oliveira; Delamaro, Marcio Eduardo; Masiero, Paulo Cesar (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
The software used to control autonomous vehicles is a type of embedded system that needs to undergo strenuous testing before deployment. Field testing is the final stage of testing ensuring that autonomous vehicles show the intended behavior. It usually does not take into consideration the code structure. In this context, a previously proposed testing model and a software tool to support structural testing in the context of autonomous vehicle field testing have been improved to support the generation of new input data from logs collected during field testing using strategies of combination and mutation. Two strategies and an exploratory study to assess their coverage according to the criteria all-nodes and all-edges are presented.